Pengaruh Gerakan Sholat Terhadap Peningkatan Fleksibilitas Otot Punggung Bawah - PRASETYONO, Eko Rahmadhon; , Wahyuni.S.Fis.,SKM.,M.Kes; , Umi Budi Rahayu, S.Fis, M.Kes (2015)
Background: Prayer is a movement that starts from the movement stood then bent, so that the hand holding the knee continued to stand back with tuma'ninah or kusyuk. True prayer movement that can give effect to the flexibility of the lower back muscles, with the main emphasis on the lower back muscle area were conducted with a frequency of at least 3-6 times a week, with a duration of 10-30 seconds for each movement, the intensity of 30-45 repetitions minutes for each prayer, from the observation that researchers found Tahajjud prayers appropriate to be used as research trials due to contraction in the static type ruku'dan movement prostrate with the main emphasis on the lower back muscle area. Objective: To determine differences in the effect of the prayer movement mandatory and obligatory prayers + Tahajjud to lower back muscle flexibility. Methods : This study used a method Quasi Experiment with pre- and post-test design with control. This study aims to determine the symptoms or effects arising from the presence of certain treatments and all variables can not be controlled by the researcher. Then do the pretest and post-test before treatment after treatment less than 1 month. Results and conclusions : The data were processed with SPSS 16 to determine the effect of the prayer movement to increase the flexibility of the lower back muscles to do nonparametric statistical test with Mann-Whitney test methods and found no significant difference between obligatory prayers with the obligatory prayers and Tahajjud to lower back muscle flexibility.